DIVANU LUGATI'T-TURKISH FOLK MEDICINE MAGIC AND RATIONAL METHODS OF TREATMENT - Navro’z Ro’ziyev Ixtiyor o’g’li (Western European Studies, 2023)
In the work "Divonu Lugati't-Turk" written by Kashgarli Mahmud in the 19th century for the purpose of preparing a dictionary, various topics related to Turkish history, geography and culture were directly or indirectly addressed with words at the beginning of the article. One of the topics that Divanu communicated and addressed with Lugati't-Turk was folk medicine. Folk medicine, called by different names, arose as a result of concern for the protection, protection and treatment of the people and developed its own methods of treatment. Folk medicine treatments are formed around magical and rational processes and practices. Dîvânu Lugâti't-Turk, which is an encyclopedic dictionary in terms of its content, has a rich collection of medical terminology and a serious world of concepts. However, among these, treatment methods require special attention and classification in terms of quality. This requirement forms the starting point of this study. Therefore, in this study, an answer to the question, "Which of the folk medicine treatments presented in Divanu Lugati't-Turk" is magical and intelligent?
Keywords: Divanu Lugati’t-Turk; folk medicine; treatment